Exploration of communication process using Business Microscope® - Chen, Y.Y. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper describes first results of ongoing research effort to investigate communication pattern within a procurement process in an organization. Previous studies have shown that the main reasons of long ordering cycle are it takes too long to deal with purchase order and unable to share information with vendors. The procurement process of an educational institution is chosen as a research sample. In this paper, we outline the opportunities for developing a future possible theoretical framework around the construct of effective communication pattern with the usage of Business Microscope®. In particular, we are able to identify typical communication patterns between inter- and intra-departments. We aim to explore the communication process that integrates efficient modes of communication that will influence and regulate the communication process. © 2014 IEEE.